Transformation of solid and liquid wastes into fertiliser to minimize urban catchment pollution - Nartey, Eric Gbenatey (Cranfield University, 2024)
Decentralised treatment systems play a critical role in managing faecal sludge (FS) in sub-Saharan Africa (SSA) where safely managed sanitation is lagging with 79% of the population without it. The systems that treat FS and food waste (FW) into faecal derived fertilisers (FDFs) play a more critical role in linking safely managed sanitation to improved food security. To recover nutrients and organic matter to their fullest potential is urgent in the context of SSA. The International Water Management Institute (IWMI) and partners have led research to convert urban FS and FW through co-composting into various FDF for use in agriculture. Though some strides have been made in developing and commercialising FDF, there are still some research and knowledge gaps including limited information on nutrient and pathogen flow in the decentralised FS and FW treatment system; limited information on the shelf life of stored FDF and on residual effect of FDF application on crops and soil. Hence, this study aimed to generate new knowledge and understanding on the recovery of nutrients and E. coli inactivation during treatment and use of fertiliser produced from FS and solid waste. The methodology involved different experimental set-ups to collect primary data. This followed an end-to-end monitoring of FS and FW treatment to produce FDF, storage of FDF and the use of the FDF in successive lettuce cultivation. Findings from this study, show that between 50-70% of total N from FS is lost at the dewatering stage of treatment. More than 50% of total N is lost during co-composting. While E. coli inactivation efficiency of the dewatering process is minimal (0-14%) in the percolate, dewatered FS on the other hand observed higher E. coli inactivation efficiency of 88-98% (1-2 log reductions). Inactivation efficiency of co-composting stage for E. coli was 100%. No detectable presence of indigenous E. coli was observed in FDF at the end of storage. Storage temperature and duration did not affect re-growth of indigenous E. coli in co-composted FDF. Longer storage of enriched FDF co- compost (NECo) under lower temperatures resulted in decreasing NH4-N concentrations. The field experiment show, residual effect of FDF co-compost (Co) gave lettuce yield of 344% more compared to the control by the second cycle. E. coli was absent on lettuce after successive cultivations. Co plots had higher gross margins/profit per cycle of cultivation. The ROI for Co was 385.7 for first cycle and 309.2 for second cycle.
Keywords: faecal sludge; nutrients; faecal derived fertiliser; pathogen; storage; lettuce